Relics of laterites on the Letovice Crystalline Complex, Moravia - Grygar,T.; Kral,R.; Nekovarik,C.; Zelenka,P. (Journal of the Czech Geological Society, 1997)
Pre-Upper-Cretaceous laterites from the Letovice Crystalline Complex (north of Brno, Moravia) were studied using phase and chemical analysis. Iron oxides were characterized also by their dissolution kinetic. Results were compared with previous works dealing with laterites in this region as well as with laterization in general. Letovice laterites are represented by both typical well preserved mixtures of kaolinite and goethite (2 localities) and recrystallized pisolitic matter composed of Al, Si and Fe oxides (1 locality).
Keywords: laterite; Letovice; Moravia